Printing ultrathin Quasi-2D Ga2O3 for fast yet highly responsive vertical photodetectors - Qian Li; Ruofan Li; Xueqing Chen; Minghui Guo; Jing Liu; Xianwei Meng (npj 2D Materials and Applications)
Abstract UV detectors have the advantages of simple signal processing, low false alarm rate, and strong anti-interference capability, and are widely used in both defense and civil applications. Gallium oxide (Ga2O3) holds great promise for photodetection, but its slow response rate hinders practical applications, so fast-response alternatives are urgently needed. Here we demonstrated ultrathin quasi-two-dimensional (2D) Ga2O3 vertical UV photodetectors with short channel lengths constructed via liquid metal printing strategy for the first time. The device achieves ultrafast response time (≈1.18 μs), high detectivity (≈2.8 × 1013 Jones), large switching ratio (~107), and low dark current (≈10 pA), which is comparable to commercial materials, demonstrating its considerable capability for photodetection technology field. This high-performance and low-cost photodetector based on liquid metal printing process provides a successful start for a wide range of applications of Ga2O3 in UV detection. It demonstrates the great potential of novel quasi-2D Ga2O3 devices for next-generation photodetection technologies.